2021
DOI: 10.1111/jfbc.13937
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock treatment maintains the quality attributes of postharvest jujube fruits and delays their senescence process during cold storage

Abstract: The effects of heat shock (HT), 1-methylcyclopropene (1-MCP), or their combination (HT + 1-MCP) on the quality of fresh jujube fruits during cold storage were studied. Among them, HT showed the best preservation effect on jujube fruits, which was more effective than others in inhibiting the increase of red index, decay incidence, and weight loss and delaying the decrease of firmness, soluble solids content (SSC), titratable acidity (TA), and ascorbic acid (AsA) content. Besides, it could delay the degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition, most fruits lose weight during storage; excessive weight loss causes obvious epidermal shrinkage, wilting, and reduction of tissue hardness [ 21 ]. Appropriate postharvest treatments effectively decrease the physiological metabolism, reduce water loss, and maintain a generally stable nutrient content and appearance [ 22 ]. Kartal et al [ 23 ] showed that a polypropylene microporous membrane (pore size 90 μm, hole number 9) combined with a deoxidizer effectively maintained the pH, SS content, electrical conductivity, and sensory quality of strawberries at 4 °C; it extended the shelf-life of strawberries longer than 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most fruits lose weight during storage; excessive weight loss causes obvious epidermal shrinkage, wilting, and reduction of tissue hardness [ 21 ]. Appropriate postharvest treatments effectively decrease the physiological metabolism, reduce water loss, and maintain a generally stable nutrient content and appearance [ 22 ]. Kartal et al [ 23 ] showed that a polypropylene microporous membrane (pore size 90 μm, hole number 9) combined with a deoxidizer effectively maintained the pH, SS content, electrical conductivity, and sensory quality of strawberries at 4 °C; it extended the shelf-life of strawberries longer than 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of visual appearance during cold storage is closely related to weight loss and firmness, which severely affect taste and economic value of post-harvest fruits and vegetables ( Fernández-León et al, 2013 ; Selahle, Sivakumar & Soundy, 2014 ). Some metabolic activities, such as transpiration and respiration, the main factors influencing the increase of weight loss and decrease of firmness with the extension of storage time, occurred in postharvest jujube fruits ( Lufu, Ambaw & Opara, 2020 ; Park et al, 2015 ; Yang et al, 2021 ). Recently, studies on strawberry ( Liu et al, 2018 ), pitaya ( Ba et al, 2021 ), peach ( Gao et al, 2016 ) and plum ( Yan et al, 2022 ) showed that exogenous melatonin significantly inhibited the increases in decay and water loss, and the decline in firmness.…”
Section: Discussionmentioning
confidence: 99%
“…Ten jujube fruits were weighed using a digital scale (Practum224-1CN; Sartorius, Göttingen, Germany). The weight loss was calculated by the following formula ( Yang et al, 2021 ). …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the maximum weight loss observed during prolonged storage can be attributed to the process of respiration or the breakdown of complex compounds into simple compounds with low molecular weight (Anggraeni, 2021). Senescence processes in cut stems lead to consuming stored food in jujube fruit (Yang et al, 2021).…”
Section: Weight Of Fronds After Storage/weight Change (%)mentioning
confidence: 99%